Energetic lipid responses of larval oysters to ocean acidification. (July 2021) - Gibbs, Mitchell C.; Parker, Laura M.; Scanes, Elliot; Byrne, Maria; O'Connor, Wayne A.; Ross, Pauline M.
Abstract: Climate change will increase energetic demands on marine invertebrate larvae and make planktonic food more unpredictable. This study determined the impact of ocean acidification on larval energetics of the oysters Saccostrea glomerata and Crassostrea gigas . Larvae of both oysters were reared until the 9-day-old, umbonate stage under orthogonal combinations of ambient and elevated p CO 2 (340 and 856 μatm) and food was limited. Elevated p CO 2 reduced the survival, size and larval energetics, larvae of C. gigas being more resilient than S. glomerata. When larvae were fed, elevated p CO 2 reduced lipid levels across all lipid classes. When larvae were unfed elevated p CO 2 resulted in increased lipid levels and mortality. Ocean acidification and food will interact to limit larval energetics. Larvae of S. glomerata will be more impacted than C. gigas and this is of concern given their aquacultural status and ecological function. Highlights: Climate change will limit larval energy of the oysters Saccostrea glomerata and Crassostrea gigas . This may impact on larval survival and ultimately aquaculture of two iconic species. Ocean acidification reduced lipid levels across all lipid classes.